Efektivitas Teknik Behavior Contract dalam Meningkatkan Ketahanan Duduk pada Anak Attention Deficit Hyperactivity Disorder Kelas XI di SMALB Negeri 14 Takengon - Dahlia, Rika; Z, Martias (Jurnal Penelitian Pendidikan Khusus, 2021)
One of the obstacles experienced by ADHD children is the low duration of sitting endurance for ADHD children. This problem was found in SMALB Negeri 14 Takengon. Where children with ADHD have a low duration of sitting endurance in sitting endurance. Behavior contract technique was able to improve sitting endurance in class XI ADHD children at SMALB Negeri 14 Takengon. This study focuses on measuring the duration of sitting endurance during the intervention using the behavior contract technique. Researchers and children will start learning with the behavior contract technique. The research method used is the, namely SSR (Single Subject Research) using the ABA design, at baseline (A1) was carried out for six meetings, then the intervention condition out for eight meetings and at the final baseline (A2) was conducted five times.The data collection method in this study used event recording by calculating how long the duration of sitting endurance was based on direct observations made. Analyzed data using with visual and graphic analysis. Result from study stated that the behavior contract technique can increase the duration of the child's sitting endurance during the learning process.